Personality and education: associations between personality dimensions, academic field of study, and performance in upper secondary school and higher education - Mikkel M. Thørrisen; Talieh Sadeghi (Cogent Psychology)
Educational choices and academic success shape individuals’ career paths and lifelong achievements. The aims of this study were to explore (a) associations between Big Five personality dimensions and academic performance in upper secondary school, (b) associations between personality dimensions and academic performance in higher education, and whether these associations differed according to academic field of study, and (c) whether students differed on personality dimensions according to academic field of study in higher education. In this cross-sectional retrospective study, data on Big Five personality dimensions, students’ chosen academic field of study, and their academic performance (average grades) were collected from 4409 master’s graduates in Norway by means of a national survey. Data were collected in 2019, approximately three years after participants had graduated. Regression analyses revealed that higher performance in upper secondary school was associated with higher conscientiousness and lower openness, while higher performance in higher education was associated with higher conscientiousness, higher openness, and lower emotional stability (higher neuroticism). Associations between personality and academic performance were generally weak and differed somewhat between academic fields of study. Results from analyses of covariance demonstrated significant differences on all five personality dimensions across students’ academic fields of study. Taken together, the present study indicates that personality may play a modest yet significant role in students’ educational choices and academic performance. Educational institutions, teachers, and students may benefit from taking personality into account in educational settings.